Colegios privados de bajo costo ¿Mejor educación a un precio razonable? Aproximación desde los resultados en Matemática en la evaluación censal de estudiantes 2016 - Marcos Balabarca, Manuel M. (2017)
This research analyzes the participation of the private sector within the education system. In this sense, it seeks to identify the characteristics of private schools and how they contribute to the development of learning by the students they serve. For this, a probabilistic model is proposed using the data of the census evaluation of students (ECE) of the year 2016 made in 2nd grade of primary education carried out by the Ministry of Education. The investigation was carried out in Lima Metropolitana.